Effective Strategies in the Financial Management of Islamic Educational Institutions: Identifying Sources and Optimizing Management - Nurul Mawaddah Al-Mursal; Hamdi Abdul Karim; Hafiz Azhari (Jurnal Bina Ilmu Cendekia, 2025)
Financing management is one of the crucial aspects in the sustainability of Islamic educational institutions. Challenges in obtaining and managing effective funds, both from internal and external sources, often become obstacles in realizing the goals of quality education. This article aims to identify various sources of financing that can be optimized by Islamic educational institutions and provide financing management strategies that are in accordance with sharia principles. Internal financing sourced from tuition fees and business units, as well as external financing such as zakat, infaq, sadaqah, productive waqf, and grants, are the main components discussed. Effective management strategies include participatory budget planning, financial transparency, and the implementation of digital systems in financial management. The article also points out the importance of diversifying revenue sources to reduce dependence on a single source of financing. Equipped with case studies and examples of best practices from successful Islamic education institutions, this article provides recommendations for managers of Islamic education institutions to strengthen their financial systems, improve accountability, and ensure financing sustainability through digital-based innovation and creative economy.